51Cr release microassay for measuring cell-mediated immunity in chickens. - Radwan, A I (1975)
A microcytotoxic assay, based on the release of 51Cr from chicken erythrocytes by sensitized chicken lymphoid cells in the presence of the specific antigen, purified protein derivative (PPD), is described. The percentage of antigen-specific lysis was dependent on the lymphoid cell concentration, antigen concentration, time of incubation, and incubation temperature. Maximum antigen-specific lysis of nonspecific target cells was induced with a spleen-to-target cell ratio of 100:1 and with a peripheral blood lymphoid-to-target cell ratio of 1,000:1 in the presence of 100 mug of PPD per ml over a 20-h incubation period. As the concentration of PPD was increased from 25 to 200 mug/ml the specific lysis that incubation for 20 h. Incubation at 41 C produced significantly higher (P smaller than 0.05) antigen-specific cytotoxicity than incubation at 37 C.